PEMETAAN KOMPETENSI GURU BERSERTIFIKAT PENDIDIK UNTUK PEMANFAATAN MEDIA TIK DALAM KEGIATAN PEMBELAJARAN DI SEKOLAH DASAR - Erna Yayuk (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Learning through the media of information and communication technology is expected for children to be intelligent, critical, and creative, and able to solve problems relating to everyday life. Awareness of teachers to improve the quality of education through the medium of ICT is the integration in the achievement of life skills as the main orientation of educational purposes. This study uses a qualitative descriptive analysis technique, with 28 research subjects of certified educators in elementary school Singosari. The result showed that teachers already know about the media ICT learning through workshops conducted by the Ministry of Education, Books, Training and seminars as well as through training when taking part the teacher certification. Keywords: Teachers with Certified Educators, Media ICT, Learning SD